Effects of Formic and Propionic Acid as Silage Additive on Haematology and Biochemical attributes in Growing Cattle - ., Vivekanand; Kumar, Muneendra; Kumar, Vinod; Kushwaha, Raju; Vaswani, Shalini; Kumar, Avinash; Shukla, Pankaj Kumar; Sirohi, Rajneesh (Indian Journal of Animal Nutrition, 2020)
This study aimed to evaluate the effect of formic and propionic acid, alone or in combination as silage additive on haematological and biochemical attributes in growing Sahiwal cattle. A total of 24 growing Sahiwal heifers were randomly allocated into four groups (n=6) on body weight (117Â±5.0 kg) and age (10Â±2.0 months) basis. The experimental heifers either received a basal total mixed ration (TMR) having ensiled sorghum fodder without organic acids (SC) or were fed on TMR having silage preserved with 0.5% formic acid (S0.5%FA), 0.5% propionic acid (S0.5%PA) or 0.25% formic acid and 0.25% propionic (S0.25%FA+0.25%PA). Feeding of silage treated with formic and propionic acids did not exert any effect on dry matter intake (DMI) while average daily gain (ADG) and feed efficiency were better (P